TINGKAT PEMANFAATAN PERPUSTAKAAN STIKES WIRA HUSADA OLEH MAHASISWA DIPLOMA III KEPERAWATAN STIKES WIRA HUSADA BULAN AGUSTUS – SEPTEMBER 2010 - Antok Nurwidi Antara (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2016)
ABSTRACTBackground: Library is the cor of the School include School of Heatlh Sciences Wira Husada Yogyakarta. The  beneﬁ cient of library by civitas academic School of Health Sciences Wira Husada, include the  Students of Nursing Diploma III, important to know the terrace,is high or low.  The goal of this research is to know how high the terrace of beneﬁ cient library in School of Health Sciences Wira Husada, expecialy by students of Nursing Diploma III School of Health Sciences Wira Husada .Methode of this research is by giving cuesioners to 95 research respondens for ﬁ iled in, and by seeing data of coming in the School of Health Sciences Wira Husada’s library.The result is  that the terrace of beneﬁ cient library by 95 research respondens,from the ﬁ illing cuesioners that1 include the knowing of library in School of Health Sciences showing  Medium category, is 70,53 %.This result showing that research respondens knowing the library is medium. Because of that, they are enough in take beneﬁ t from School of Health Sciences Wira Husada’s library. The respondents knowing of : Rules in the School of Health Science Wira Husada’s library, the category is medium, about : 61,58 %, showing  that the respondents enought know the rules, and get beneﬁ t enought from the rule in the library. The almost book that is read or borrowed are: Anatomi book, the percentase is : 27,78 %, after that the book of Basic Human Need, the percentase is 31,43 %, after that the book of Maternity and Medical Surgical Nursing the percentase is 30,30 %. The total Visiting to the library in August and September 2010 is 8 people per day.The conclution: that the research report is Student of Nursing Diploma III School of Health Science “Wira Husada”, enought in have beneﬁ t the library, because of that important to tell the civitas academica expecially student of Nursing Diploma III for visiting the library to study.The suggest: that important to improve the facilities and the service in the library, that  can make the civitas academica love to visiting the library on School of Health Science Wira Husada Yogyakarta.